The Effect of Sunkist Orange (Citrus Sinensis (L.) Osbeck) Peel Granule Extract on Testicular Histophatology in Male Rats (Rattus Norvegicus) with Obesity - Mutia, Maya Sari; Br Sitepu, Rachel Maria Cruz Jovanca; Putri, Shafyra Mahdyah; Gurusinga, Fransisco Bastanta; Lubis, Yolanda Eliza Putri (AVERROUS: Jurnal Kedokteran dan Kesehatan Malikussaleh, 2025)
Obesity is a body condition where there is excessive weight gain due to an imbalance between calories consumed and energy expended so that calories accumulate in fat tissue. In Indonesia, there are 14.8% of the population aged > 18 years who are obese. The basic principle of obesity is that there is an imbalance between three aspects, namely food intake (intake), energy expenditure (output), and energy storage. The result of the imbalance in energy intake and output, where energy intake is greater than energy expenditure, will cause the accumulation of fat tissue in the body and will be stored as energy reserves. Obesity is a predisposing factor for various health problems. One of them is the quality of a person's reproduction which results in infertility. To find out that the extract of sunkist orange peel granules can affect the histopathology of testis in male mice with obesity, this study used an in vivo laboratory experimental method with a research design of Post Test Only Control Group Design. In this study, there were 25 male rats divided into 5 groups, with a negative control group (normal rats without treatment), a positive control group (rats induced with high-fat feed), a treatment group of rats induced with high-fat feed with Sunkist orange peel extract granules (Citrus Sinensis (L.) Osbeck) at a dose of 50 mg/KgBW, 100 mg/KgBW, and 150 mg/KgBW. Conclusion: Sunkist orange peel granule extract (Citrus Sinensis (L.) Osbeck) had an effect on blood glucose levels, total cholesterol, and body weight, but did not show a significant effect on the histopathological results of the testes in male rats.